1993
DOI: 10.1023/a:1018945902276
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Uptake of the nonabsorbable marker 6-carboxyfluorescein was investigated both free and encapsulated in liposomes as a function of their surface charge and hydrodynamic diameter in rat Peyer's patch and nonpatch tissue. Significant uptake of the marker occurred only when encapsulated in liposomes consisting of at least 25 mol% phosphatidylserine and was highest in Peyer's patches. 6-Carboxyfluorescein encapsulated in liposomes equal to or greater than 374 nm was preferentially taken up by Peyer's patches. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…, 186. , and the liposomal surface charges influenced the efficency 187 . In addition, prolonged residence of liposomes in GIT increases the opportunity of uptake by M cells 188.…”
Section: Mechanisms Of Oral Absorption Of Liposomesmentioning
confidence: 99%
See 1 more Smart Citation
“…, 186. , and the liposomal surface charges influenced the efficency 187 . In addition, prolonged residence of liposomes in GIT increases the opportunity of uptake by M cells 188.…”
Section: Mechanisms Of Oral Absorption Of Liposomesmentioning
confidence: 99%
“…Therefore, M cells are easily accessible for liposomes via mechanisms of adsorptive endocytosis, fluid phase endocytosis and phagocytosis 185 . It was shown that the M cell pathway contributes to total oral absorption of liposomes57., 186., and the liposomal surface charges influenced the efficency 187 . In addition, prolonged residence of liposomes in GIT increases the opportunity of uptake by M cells188., 189., which partly explains the contribution of stabilization of liposomes to enhanced oral absorption69., 95..…”
Section: Mechanisms Of Oral Absorption Of Liposomesmentioning
confidence: 99%
“…The uptake of particles is reported to primarily occur via the M cells [2], which have been referred to provide a privileged contact with mannose residues [14,15] and, therefore, might be used as privileged target for mannose-containing particles. Locust bean gum (LBG) is a polysaccharide of the class of galactomannans, thus having a chemical structure composed of both galactose and mannose units [16] (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports on the intact liposomal uptake by cells in in vitro and in situ experiments5658. The results are, however, not convincing for the oral delivery of protein with a liposomal system.…”
Section: Pharmaceutical Approachesmentioning
confidence: 98%